Labelling requirements of genetically modified food in Malaysia: a comparative study with The United Kingdom / Ahmad Yazid Alrafiq lsmail, Mohd Nasrizal Md Akil, Muhammad Fadzlan Mohd Noor - lsmail, Ahmad Yazid Alrafiq; Md Akil, Mohd Nasrizal; Mohd Noor, Muhammad Fadzlan (2011)
Genetically Modified Food (GM food) is something new7 in the food industry and the labelling of GM food seemed to be very fundamental. It is because labelling GM food provides consumers on the freedom of choice. The significant of this study is to highlight the loophole in Malaysian law with regard to the issue on the labelling of GM food. The laws that govern this area are the Biosafety Act 2007 and the Food Act 1983. The law pertaining to the labelling of GM food is still lacking specifically in the Food Regulations 1985. Even though there were amendments in the regulations with regard to the manner GM food should be labelled; the law is still silent on the issue of exception to the mandatory labelling, pre-packaged and non pre-packaged food; and guidelines in the matter of labelling of GM food that manufacturer should comply with. Since Malaysia had ratified the Cartagena Protocol on Biosafety to the Convention on Biological Diversity, Malaysia is obliged to follow7 the labelling requirements of GM food as provided by the Convention. It was also found that the non-compliance of the labelling requirements of GM food might associate with many disadvantages to the consumers especially on the health risks, religion and vegetarian aspect and also consumers' freedom of choice. This study used the qualitative methodology which includes library-based research. All in all, it is very much recommended that the existing law be amended to overcome the issue on labelling of GM food especially regarding the exception to the mandatory labelling, pre-packaged and non pre- packaged food as well as the guidelines that manufacturers of GM food should follow.